Clinical and Economic Management of Uterine Fibroids: The Point of View of a Decision Makers Board. Issue 3 (November 2016) - Di Carlo, Costantino; Maiorana, Antonio; Poidomani, Ignazia; Ravasio, Roberto; Vercellone, Adriano
Uterine fibroids can have a significant economic impact on the National Healthcare Service and on Society overall (absenteeism and disability). Women with uterine fibroids have higher use of medical services and procedures. The management and treatment of uterine fibroids thence imposes a burden on the existing National Healthcare Service and it is important to understand the economic implications between treatment options and key cost drivers. Our analysis is limited to describe the disease management and pharmacological costs of uterine fibroids. Our focus is on clinical data, therapeutic options, treatment costs and unmet needs (therapeutic diagnostic path). Knowledge of these aspects can be a useful tool for the clinician in order to select the most effective treatment in clinical practice, tailored on patients' characteristics.